Pelatihan Penggunaan media Loose Part Sebagai Implementasi Merdeka Belajar Pada Satuan Pendidikan Anak Usia Dini - Andari, Ida Ayu Made Yuni; Meriah, Eri (IAHN Gde Pudja Mataram, 2023)
Early childhood education teachers play a vital role in the development and education of young children. They have broad and varied responsibilities in creating positive learning environments and facilitating children's holistic development. Early childhood education teachers are key facilitators in children's learning process. They create learning experiences that are engaging, stimulating and appropriate to children's needs and interests. Teachers help children to explore, think critically and build an understanding of the world around them. This service has the aim of increasing teachers' understanding related to an in-depth understanding of the loose parts method. This service method consists of lecture, discussion, demonstration, hands-on practice and question and answer methods. The importance of the results of this service is to develop innovative teaching skills, increase cognitive stimulation and creativity, improve the use of environmental resources, collaboration and exchange of experiences. The results of this service are divided into two sessions. Session 1 is the lack of facilities and facilities and the lack of awareness and interest of local communities in the importance of early childhood education and the lack of interest in becoming early childhood educators. In session 2, there is a need for follow-up such as training, workshops and materials related to the theme of Loose Part media for early childhood. Through community service, teachers in the Loose Part media method in early childhood, teachers can improve their competence in dealing with today's educational demands, create innovative and child-centered learning experiences, and facilitate the holistic development of children in early childhood.